THE ROLE OF HOSPITALS IN PROTECTING HEALTH WORKERS FROM VIOLENCE BY PATIENTS/PATIENT FAMILIES AT MELAWI REGIONAL HOSPITAL: A STUDY IN THE INTERNAL MEDICINE WARD - Chandra Dewi; Dahlan; Henry Aspan (RADJA PUBLIKA, 2025)
Legal protection is a right owned by health workers and medical personnel, in accordance with Law no. 17 of 2023 on Health Article 273, hospitals have an obligation to protect staff who work when experiencing disputes, as long as they are in accordance with operational standards when working. This study aims to examine and analyze the regulations on legal protection of health workers and medical personnel, as well as the role of hospitals in acts of violence that occur at Melawi Regional Hospital. The research method is qualitative analysis with an empirical legal approach. The data sources used are primary data consisting of case observations, questionnaires and interviews at Melawi Regional Hospital, while secondary data is obtained from books, laws, cases and document data available at the hospital. The results of the study at Melawi Regional Hospital, problem solving will be carried out by the existing public relations/case manager team, but the Regional Hospital has not provided legal assistance/advocates. For problem solving, it is carried out through mediation/non-litigation, but without legal counsel.